1998
DOI: 10.1021/jm980022k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 9-Deoxo-4‘‘-deoxy-6,9-epoxyerythromycin Derivatives:  Novel and Acid-Stable Motilides

Abstract: In our quest toward the discovery of highly potent and acid-stable motilides, novel 4"-deoxy derivatives of 9-deoxo-6, 9-epoxyerythromycin were designed, synthesized, and evaluated for their gastrointestinal prokinetic activities. These compounds, in their 9R configuration, were more potent than their 6,9-enol ether homologues in inducing well-coordinated smooth muscle contractions in an in vitro rabbit duodenal assay: e.g., (9R), (8S)-9-deoxo-4"-deoxy-3'-N-desmethyl-3'-N-ethyl-6, 9-epoxyerythromycin A (10) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…The cell line was used to evaluate a panel of test compounds and provided EC 50 values for receptor activation that agree with data reported in contractility assays and data obtained using HEK293 cells transiently transfected with the native human motilin receptor cDNA (8,14,24,27). The K i value obtained for receptor antagonism by ANQ11125 also correlates with contractility measurements and further validates the physiological relevance of the system (24).…”
Section: Discussionsupporting
confidence: 69%
“…The cell line was used to evaluate a panel of test compounds and provided EC 50 values for receptor activation that agree with data reported in contractility assays and data obtained using HEK293 cells transiently transfected with the native human motilin receptor cDNA (8,14,24,27). The K i value obtained for receptor antagonism by ANQ11125 also correlates with contractility measurements and further validates the physiological relevance of the system (24).…”
Section: Discussionsupporting
confidence: 69%
“… 43 It was also able to reduce gastro‐oesophageal reflux under various conditions in some studies 14 . As in vitro and invivo experiments have demonstrated that ABT‐229 has a 10–1000 times more potent prokinetic effect than erythromycin, 18–22 the results of our study and that of Van Herwaarden et al 36 . on the lower oesophageal sphincter and oesophageal motility are disappointing.…”
Section: Discussionmentioning
confidence: 63%
“…Because erythromycin also has an antibacterial effect, new motilides with motilin agonist activity but no antibiotic activity were searched for, which led to the discovery of ABT‐229 18 ,. 19 This erythromycin derivative also binds to motilin receptors and in both in vitro and in vivo studies it was 10–1000 times more potent as a prokinetic agent than erythromycin 18–22 . It has been shown that ABT‐229 accelerates gastric emptying in healthy subjects 23 and increases the lower oesophageal sphincter pressure in cats 24…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of 9-deoxo-4′′-deoxy-6,9-epoxyerythromycin derivatives was recently reported [101]. For example, compound 38 was found to have superior in vitro activity as a motilide compared to an earlier analogue, ABT-229.…”
Section: Non-antibacterial Uses Of Macrolidesmentioning
confidence: 99%